Contrasting the role of the serendipity in austrian and neoclassic theories - Marion Ceolin, Artur (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
The serendipity, as likes as any another change, is a constant in the human action and we are not lacking examples in the history, as the discovery of the penicillin, to see its great importance role at the innovation process. But, despite this importance, the serendipity is excluded of the neoclassic models, because of its static equilibrium approach and also for the treatment of knowledge. On the other hand, the Austrian methodology, for considering the dinamic efficience, the market as a process, the future as something to be made and the knowledge as disperse and to be discovery, it’s the best approach for the investigation of the occasional generation of innovation, called serendipy.